Hak Kepemilikan Harta Dalam Al-Qur’an - Ahmad Royhan Firdausy; Zainol Hasan; Supriyadi (STIS DAFA MATARAM, 2024)
This study aims to examine the concept of property ownership rights in the Qur'an, emphasizing the balance in life through the management of wealth for collective well-being. Islam acknowledges the natural human inclination toward owning wealth but establishes regulations to ensure that ownership benefits not only individuals but also the broader community. This research employs a descriptive-analytical method with a library research approach. Primary sources include the Qur'an, Hadith, and tafsir texts, supplemented by relevant supporting literature. The findings reveal that Allah SWT is the ultimate owner of all that exists in the heavens and the earth (QS. Al-Maidah: 120), while humans are entrusted with temporary ownership to sustain their livelihoods (QS. Al-Hadid [57]: 7). This ownership is categorized into three types: individual ownership, acquired through work (QS. Al-Jumu'ah [62]: 10) or inheritance (QS. Al-Baqarah [2]: 180; QS. An-Nisa’ [4]: 11-12); state ownership, which includes zakat, ghanimah, and fa'i (QS. Al-Anfaal [8]: 41; QS. Al-Hasyr [59]: 7); and public ownership, encompassing resources managed for communal benefit (QS. Ar-Rahmaan [55]: 10). This study contributes to the development of Islamic economic theory by emphasizing the importance of equitable wealth distribution and providing practical foundations for economic policies grounded in Qur'anic values to achieve collective prosperity.